Catheterization‐based intervention in low birth weight infants less than 2.5 kg with acute and long‐term outcome. Issue 5 (1st July 2013) - Kobayashi, Daisuke; Sallaam, Salaam; Aggarwal, Sanjeev; Singh, Harinder R.; Turner, Daniel R.; Forbes, Thomas J.; Gowda, Srinath T.
<x xml:space="preserve">Abstract</x> Background The number of low birth weight infants with congenital heart disease is increasing and catheterizations may have an increased risk for mortality and morbidity. Objectives We investigate the outcome and complications of cardiac catheterizations in infants weighing < 2.5 kg. Methods Retrospective review of catheterization records from 1995 to 2010 in infants weighing < 2.5 kg. The demographics, procedure, outcome, and follow‐up data were collected. Results Of 101 catheterizations performed in 88 patients, 45 (45%) catheterizations were interventional. Balloon atrial septostomy (n = 23), pulmonary valvuloplasty (14), aortic valvuloplasty (4), stent placement (3), balloon angioplasty (2), and temporary pacemaker insertion (1) were successfully performed. Balloon atrial septostomy was performed with pulmonary or aortic valvuloplasty in two catheterizations. Infants < 2.5 kg had higher significant adverse event rate that those 2.5−3.5 kg (13% versus 6.6%, P < 0.05). No procedural death was noted. Significant adverse events (n = 13) included cardiopulmonary resuscitation three, vascular six, arrhythmia three, and apnea requiring intubation one. On median follow‐up of 3 years (0.03 to 14), n = 69, mortality rate was 36%. In six patients with valvar pulmonary stenosis with median follow‐up of 6 years (0.75–13), four (67%) did not require re‐intervention. Of two patients with aortic stenosis, one did not require repeat intervention for 6 years (last follow‐up). Conclusion Interventional catheterization is feasible with low procedural morbidity and mortality in high risk infants < 2.5 kg. Catheterization primarily serves as a palliative procedure to stabilize infants for definitive treatment. Balloon valvuloplasty may be effective for isolated valvar pulmonary stenosis in infants < 2.5 kg. © 2013 Wiley Periodicals, Inc.